Effects of high‐dose statin on the human hepatic expression of genes involved in carbohydrate and triglyceride metabolism - Pramfalk, C.; Parini, P.; Gustafsson, U.; Sahlin, S.; Eriksson, M. (Journal of internal medicine, 2011)
.  Pramfalk C, Parini P, Gustafsson U, Sahlin S, Eriksson M (Department of Laboratory Medicine, Division of Clinical Chemistry; Department of Biosciences and Nutrition, Centre for Nutrition and Toxicology, Molecular Nutrition Unit, NOVUM; Department of Surgery, Karolinska Institutet at Danderyd Hospital, Danderyd; Department of Endocrinology, Metabolism Unit, Metabolism and Diabetes, and Department of Medicine, Karolinska Institutet at Karolinska University Hospital Huddinge, S‐141 86 Stockholm, Sweden). Effects of high‐dose statin on the human hepatic expression of genes involved in carbohydrate and triglyceride metabolism. J Intern Med 2010; 269: 333–339. Objectives:  Atorvastatin, an inhibitor of 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase, the rate‐limiting enzyme in cholesterol synthesis, lowers plasma cholesterol and triglyceride (TG) levels dose dependently. The aim of this study was to investigate the molecular mechanism(s) of this decrease in plasma TG levels in atorvastatin‐treated subjects. Research Design and Methods:  Lipoprotein separation and plasma analysis of lipids, glucose and insulin were performed in subjects randomly assigned to placebo (n = 9) or atorvastatin (80 mg per day) (n = 10) for 4 weeks. Liver TG mass was determined in pooled samples. Hepatic expression of several genes involved in carbohydrate and TG metabolism was determined. Results:  Atorvastatin lowered plasma levels of very low‐density lipoprotein (VLDL) TG (∼50%, P < 0.05) and liver TG mass compared to placebo. Except for cholesterol changes, there were no other significant differences in plasma lipids, glucose or insulin. However, atorvastatin reduced mRNA expression of sterol regulatory element‐binding protein 1c (SREBP1c) (>30%, P < 0.05), glucokinase (∼50%, P < 0.05) and angiopoietin‐like protein 3 (ANGPTL3) (∼25%, P < 0.01), and induced mRNA expression of acetyl‐coenzyme A carboxylase 1 (∼45%, P < 0.05) and glucose‐6‐phosphatase (∼90%, P < 0.05) compared to placebo. Conclusions:  Following treatment with atorvastatin, reduced ANGPTL3 mRNA expression may contribute to the reduced plasma levels of VLDL TG. The reduced liver TG mass induced by a high dosage of atorvastatin may be important for the treatment of patients with fatty liver.